2017
DOI: 10.1111/jopr.12675
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Bone Dimensions in the Anterior Maxilla: A Cone Beam Computed Tomography Study

Abstract: Labial bone thickness is thin in the vast majority of maxillary anterior teeth. Use of CBCT facilitates planning for immediate implant placement and is helpful in the decision-making process when further bone augmentation is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
29
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 37 publications
(73 reference statements)
9
29
1
Order By: Relevance
“…Based on our results, CEJ-BC distance did not exceed 4 mm in any of the reported teeth, with premolars being the only teeth presenting with this maximum distance. These findings are in agreement with other studies that reported similar CEJ-BC mean values on central incisors, lateral incisors, canines and premolars (AlTarawneh, AlHadidi, Hamdan, Shaqman, & Habib, 2018;El Nahass & Naiem, 2015;Januário et al, 2011;Wang et al, 2014;Zekry, Wang, Chau, & Lang, 2014). Furthermore, our finding that the CEJ-BC distance seems to increase with increasing age is also consistent with previous reports (Cook et al, 2011;Dos Santos, Oliveira Reis Durao, de Campos Felino, & Casaleiro Lobo de Faria de Almeida, 2019;Zekry et al, 2014) and represents the physiologic bone loss that takes place with ageing.…”
Section: Cej-bc Distancesupporting
confidence: 93%
“…Based on our results, CEJ-BC distance did not exceed 4 mm in any of the reported teeth, with premolars being the only teeth presenting with this maximum distance. These findings are in agreement with other studies that reported similar CEJ-BC mean values on central incisors, lateral incisors, canines and premolars (AlTarawneh, AlHadidi, Hamdan, Shaqman, & Habib, 2018;El Nahass & Naiem, 2015;Januário et al, 2011;Wang et al, 2014;Zekry, Wang, Chau, & Lang, 2014). Furthermore, our finding that the CEJ-BC distance seems to increase with increasing age is also consistent with previous reports (Cook et al, 2011;Dos Santos, Oliveira Reis Durao, de Campos Felino, & Casaleiro Lobo de Faria de Almeida, 2019;Zekry et al, 2014) and represents the physiologic bone loss that takes place with ageing.…”
Section: Cej-bc Distancesupporting
confidence: 93%
“…Previous reports have been performed to evaluate the bone thickness of maxillary anterior teeth [2,13,14,15]. In a majority of cases, the thickness of the labial bony wall of the maxillary anterior teeth is thin [13]. In another report, the average crestal bone thickness was 0.82 mm for the anterior maxilla [2].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, 83% and 92% of the anterior tooth had labial bone thickness 1 mm or less at the crest and middle of the root, respectively [15]. The average bone thickness at the coronal, middle, and apical thirds of the labial side of the roots was 0.73, 0.69, and 0.60 mm for the central incisor, respectively, and 0.70, 0.61, and 0.49 mm for the lateral incisors [13]. The thickness of the palatal bony wall was significantly larger than the labial bony wall [13].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations